Antifungal activity of extracts and phenolic compounds from Barringtonia racemosa L. (Lecythidaceae) - Hussin, Nurul Mariam; Muse, Radzali; Ahmad, Siti Aqlima; Ramli, Johari; Mahmood, Maziah; Sulaiman, Mohd Rosni; Abd. Shukor, Mohd. Yunus; Abdul Rahman, Mohd Fadhil; Aziz, K. N. K. (Academic Journals, 2009)
The antifungal activity of methanolic, ethanolic and boiling water extracts of Barringtonia racemosa leaves, sticks and barks were investigate against Fusarium sp., Tricoderma koningii, Penicillium sp.,Ganoderma tropicum, Ganoderma lucidum, Aspergillus sp. and Rhizopus sp. at concentration of 50 mg/ml. Better antifungal activity was observed with the methanolic extracts in all aerial parts of B.racemosa that showed excellent inhibitory activity against all the fungi tested. The strongest inhibitory activity effect was observed with the methanolic extract of leaf against Fusarium sp. (53.45%), G.lucidum (34.57%), Aspergillus sp. (32.27%) and T. koningii (20.99%). Remarkable are also the specific effects of the boiling water extract of leaf against Fusarium sp. (51.72%) and with the ethanolic extract of bark against Rhizopus sp. (37.50%). None of the boiling water extracts of leaf, stick and bark showed inhibitory activity effect against G. tropicum and T. koningii. Among different fungi tested, Fusarium sp.was found to be more sensitive to B. racemosa extracts when compared to others. The increase in the production of phenolics in the extracts can be correlated with the induction of resistance in treated plant against phytopathogenic fungi. HPLC analysis of the extract of B. racemosa (leaves, sticks and barks) showed two different phenolic acids (gallic acid and ferrulic acid) and four different flavonoids (naringin, rutin, luteolin and kaempferol). The results of present study provide scientific basis for the use of the plant extract in the future development as antifungal, antibacterial, antioxidant and antiinflammatory agent.